ETHNOMATHEMATICS MIJOU DAMAR IN CHILDREN IN DOKA BARAT VILLAGE ARU SELATAN DISTRICT - Kaliky, Sitti Hajar (Program Studi Pendidikan Matematika (Kampus Kab. Maluku Barat Daya) Universitas Pattimura, 2023)
In everyday life, education and culture are something that cannot be avoided. The purpose of this research is to describe the ethnomathematics contained in the Mijou Damar game for Doka Barat children. The population in this study were all children aged 6-12 years. Incidental sampling technique. Mijou Damar's game has the concepts of operations on integers, measurement, geometry, probability and quantifiers. The concept of integer operations when children calculate Damar. The concept of measurement and quantifier is seen when the child calculates the distance between where the Damar falls and the center of the circle. Making circles, lines and tools is an application of geometric concepts. Meanwhile, the concept of chance is seen when children can predict who will emerge as the winner and calculate the percentage probability of winning. It shows that ethnomatematics is contained in Mijou Damar.